2001
DOI: 10.1111/j.1651-2227.2001.tb00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Premature cessation of breastfeeding in infants: development and evaluation of a predictive model in two Argentinian cohorts: the CLACYD study*, 1993–1999

Abstract: The objective of this study was to develop a model to predict premature cessation of breastfeeding of newborns, in order to detect at‐risk groups that would benefit from special assistance programmes. The model was constructed using 700 children with a birthweight of 2000 g or more, in 2 representative cohorts in 1993 and 1995 (CLACYD I sample) in Córdoba, Argentina. Data were analysed from 632 of the cases. Mothers were selected during hospital admittance for childbirth and interviewed in their homes at 1 mo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…also reported that unwanted pregnancy decreased breast‐feeding 29 . There have been other studies showing that breast‐feeding was discontinued earlier in babies born to women with unplanned pregnancy 16,30 …”
Section: Discussionmentioning
confidence: 95%
“…also reported that unwanted pregnancy decreased breast‐feeding 29 . There have been other studies showing that breast‐feeding was discontinued earlier in babies born to women with unplanned pregnancy 16,30 …”
Section: Discussionmentioning
confidence: 95%
“…Other studies report that type of birth may be associated (33)(34)(35) , may not be associated (6,7,23) or may be weakly associated (36) with breast-feeding duration.…”
Section: Duration Of Breast-feedingmentioning
confidence: 99%
“…For example, studies from the United States have found that children resulting from unwanted births were less likely than those identified as wanted to be breastfed [8][9][10][11][12][13]. Additionally, studies from low-income countries in South America and West Africa have shown that compared to women who reported their births were wanted, women with unwanted births had lower likelihoods of breastfeeding and continuing to breastfeed [14][15][16][17]. Fertility intentions are also associated with several distinct indicators of child health across contexts, including higher rates of childhood illness [18], low birthweight [9,19], stunting [20][21][22], and infant mortality [21,23,24].…”
Section: Introductionmentioning
confidence: 99%